Assessing Community Resilience in Tambakrejo Village, Blitar Regency Using the Integrated Concept of Community Resilience (ICCR) Framework - Nisa, Hikmatun; Usman, Fadly; Adrianto, Dimas Wisnu (Fakultas Teknik Universitas Brawijaya, 2025)
Tambakrejo Village, located on the southern coast of Blitar, is highly vulnerable to tsunamis. The research utilizes the Integrated Concept of Community Resilience (ICCR) framework, incorporating both internal factors, such as social, economic, and cultural capital, and external factors like disaster risk governance and disaster-based spatial planning, to assess the resilience of the community. Primary data was gathered through interviews, questionnaires, and field observations, complemented by secondary data from BPBD and BPS. The analysis, based on the ICCR framework, revealed that the community resilience in Tambakrejo is at a medium level (ICCR score ranging from 30 to 60) in Social, Economic, and Cultural Capital (SCE = 56.35) and Disaster-Based Spatial Planning (DBSP = 47.22), and a high level (score above 60) in Disaster Risk Governance (DRG = 63.49). Key findings include a lack of detailed disaster risk maps and limited mitigation infrastructure, which hinder effective disaster preparedness. However, the community shows strong potential in social cohesion and culture, with active participation in disaster risk reduction activities and a high level of awareness regarding tsunami threats. This research underscores the need for sustainable economic diversification, improved evacuation infrastructure, and better integration of spatial planning in disaster mitigation efforts including capacity-building training for local disaster response teams, community workshops on risk mapping and evacuation route planning, and the development of alternative livelihoods beyond the fisheries sector to further increase community resilience against tsunami threats.